Enrichment and characterization of steroid-degrading microbes for targeted removal of steroid hormone micropollutants in small-scale wastewater treatment solutions - Kujala, Katharina; Nübel, Laura Lucia; Philipp, Bodo; Holert, Johannes (American Society for Microbiology, 2025)
In remote areas, wastewater treatment typically occurs directly at thesource in decentralized systems, which often work well in removing biochemical oxygendemand, nitrogen, and phosphorus, but not micropollutants like pharmaceuticals andsteroid hormones. Microorganisms capable of degrading such micropollutants couldbe used in bioengineered systems to increase micropollutant removal. In this study,bacteria were enriched from municipal wastewater in flow-through reactors supplemented with testosterone (TE), androsta-1,4-dien-3,17-dion (ADD), 17β-estradiol (E2), or17α-ethinylestradiol (EE2). The removal of TE and ADD was stable over multiple transfers,and several androgen-degrading Comamonas strains were isolated. In contrast, theremoval of E2 and EE2 was considerably slower, and no estrogen-degrading strains wereisolated, suggesting that estrogens were removed mainly by adsorption and precipitation rather than by biological activity. The system’s complexity was then increasedto approach real-life conditions by increasing reactor size, adding lactate and acetateas alternative carbon sources, and/or sterilized real wastewater and supplementing ahormone mix. Sequencing-based community analysis confirmed Comamonas as themain androgen degrader in these reactors but did not identify any known estrogendegraders. Alternative carbon, but not real wastewater, reduced hormone removalrates. These results show that (i) efficient androgen-degrading bacteria can be readilyisolated using flow-through reactors and low hormone concentrations, while isolationof estrogen degraders is more difficult, (ii) androgen-degrading Comamonas strains aregood candidates for bioaugmentation of small-scale water treatment solutions, and (iii)alternative carbon sources might hinder steroid degradation. This provides a basis toimprove steroid removal from wastewater by bioaugmentation to prevent hormonedischarge into water bodies.
Keywords: bioaugmentation; steroid hormones; onsite wastewater treatment; Comamonas; micropollutants